2009
DOI: 10.1111/j.1550-7408.2008.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence and Ape‐to‐Ape Transmission of the Entodiniomorphid Ciliate Troglodytella abrassarti in Captive Gorillas

Abstract: ABSTRACT. Entodiniomorphid ciliates are often present in the colons of wild apes. In captive apes the infection tends to gradually disappear, with the exception of Troglodytella abrassarti. We used fecal examinations to screen the gorillas (Gorilla gorilla gorilla) in European (Czech Republic, UK) and Australian Zoos to explore the ape-to-ape transmission pattern of T. abrassarti. Gorillas from two out of three European Zoos were positive for T. abrassarti, while gorillas from the Australian Zoo were negative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…The most prevalent protozoal species that were found in this study were ciliates; approximately 6 species were detected in the fecal sample, which is in agreement with results from previous studies that identified entodiniomorph ciliates in the majority of fecal samples that had been collected from wild western lowland gorillas at Bai Hokou, Dzanga-Ndoki National Park (Central African Republic) and the Lopé Reserve (Gabon)111213. However, our results conflict with those from the study by Modry et al 38, in which T. abrassarti was the sole entodiniomorph ciliate that was detected in captive western lowland gorillas at the Prague Zoo in the Czech Republic. T. abrassarti has also been morphologically observed in fecal specimens from wild lowland gorillas39, where it appears to play an important role in digestion because of its ability to ferment polysaccharides in the hindguts of primates40.…”
Section: Discussionsupporting
confidence: 89%
“…The most prevalent protozoal species that were found in this study were ciliates; approximately 6 species were detected in the fecal sample, which is in agreement with results from previous studies that identified entodiniomorph ciliates in the majority of fecal samples that had been collected from wild western lowland gorillas at Bai Hokou, Dzanga-Ndoki National Park (Central African Republic) and the Lopé Reserve (Gabon)111213. However, our results conflict with those from the study by Modry et al 38, in which T. abrassarti was the sole entodiniomorph ciliate that was detected in captive western lowland gorillas at the Prague Zoo in the Czech Republic. T. abrassarti has also been morphologically observed in fecal specimens from wild lowland gorillas39, where it appears to play an important role in digestion because of its ability to ferment polysaccharides in the hindguts of primates40.…”
Section: Discussionsupporting
confidence: 89%
“…Ashford et al, 2000;Dupain et al, 2009;Huffman et al, 1997Huffman et al, , 2009Krief et al, 2005;Landsoud-Soukate et al, 1995;McGrew et al, 1989;Modrý et al, 2009;Nejsum et al, 2006]. To date, however, few studies describing the parasites of chimpanzees introduced into non-native habitat have been reported [Hasegawa et al, 2005;Petrzelkova et al, 2006].…”
Section: Discussionmentioning
confidence: 91%
“…The ciliates Isotricha protostoma and Troglodytella abrassarti , distantly related to N. coli , exhibit rather low ITS polymorphism and high host specificity [50], [51]. Transmission of these ciliates is limited, due to the fragile nature of their trophozoites, to close contact between hosts [52], [53]. Higher genetic polymorphism of ITS genes of N. coli can result from transmissions facilitated by the resilient cysts of Neobalantidium .…”
Section: Discussionmentioning
confidence: 99%